Dual-color fluorescence cross-correlation spectroscopy on a Single plane illumination microscope (SPIM-FCCS) - Krieger, Jan Wolfgang; Singh, Anand Pratap; Garbe, Christoph S.; Wohland, Thorsten; Langowski, Jörg (Optics express, 2014)
Single plane illumination microscopy based fluorescence correlation spectroscopy (SPIM-FCS) is a new method for imaging FCS in 3D samples, providing diffusion coefficients, flow velocities and concentrations in an imaging mode. Here we extend this technique to two-color fluorescence cross-correlation spectroscopy (SPIM-FCCS), which allows to measure molecular interactions in an imaging mode. We present a theoretical framework for SPIM-FCCS fitting models, which is subsequently used to evaluate several test measurements of in-vitro (labeled microspheres, several DNAs and small unilamellar vesicles) and in-vivo samples (dimeric and monomeric dual-color fluorescent proteins, as well as membrane bound proteins). Our method yields the same quantitative results as the well-established confocal FCCS, but in addition provides unmatched statistics and true imaging capabilities.